2008
DOI: 10.1002/jbt.20231
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxin III‐induced apoptosis is mediated by Ca2+‐dependent caspase‐12 activation in K562 cells

Abstract: Cardiotoxin III (CTX III), a basic polypeptide with 60 amino acid residues isolated from Naja naja atra venom, has been reported to have anticancer activity. When K562 cells were treated with CTX III, cytosolic calcium concentration was rapidly and persistently increased. This CTX III-induced cell death was partially reversed by pretreatment with BAPTA/AM (20 microM), a chelator of intracellular Ca2+. Moreover, CTX III-induced apoptotic signals, such as caspase-12 and c-Jun N-terminal kinase (JNK) activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…One plausible interpretation is that mechanical overloading triggered ERS in myoblast through other mechanisms independently of calcium homeostasis, thus had little effect on calpain activation. Another possibility is that calpain could stay inactivated even when intracellular calcium concentration is high, reported by Yang, Chien, Chang, & Lin (). Besides, we do not deny that calpain might be activated and cleave caspase‐12 during stretch loading for less than 12 hr, as demonstrated by Martinez et al () that calpain preceded caspase‐7 in cleaving caspase‐12 during ERS.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible interpretation is that mechanical overloading triggered ERS in myoblast through other mechanisms independently of calcium homeostasis, thus had little effect on calpain activation. Another possibility is that calpain could stay inactivated even when intracellular calcium concentration is high, reported by Yang, Chien, Chang, & Lin (). Besides, we do not deny that calpain might be activated and cleave caspase‐12 during stretch loading for less than 12 hr, as demonstrated by Martinez et al () that calpain preceded caspase‐7 in cleaving caspase‐12 during ERS.…”
Section: Discussionmentioning
confidence: 99%
“…Number of described snake venom proteins, including metalloproteinase, disintegrin, CLP, PLA 2 and LAAO, purified from the venom of different species have been shown to induce apoptosis interacting different pathways. 12,[17][18][19][20][21][22]40 In the present study, preliminary information showing the induction of apoptosis in K562 cells after exposure to M. lebetina obtusa venom was obtained by the observation of the morphological characteristics of apoptosis as well as activation of caspase-3 by immunohistochemistry. Caspase-3 is one of the key executioners of apoptosis.…”
Section: 3639mentioning
confidence: 99%
“…32,33 There are limited studies investigating the induction of apoptosis in K562 cells, after treatment with crude snake venom or purified proteins. 14,17,19,22,38,[41][42][43] Samel et al 19 investigated the effect of Sephadex G-100 chromatography fractions of M. lebetina turanica (subspecies was not mentioned in the paper but assigned according to the locality) venom and also purified HUVEC apoptosis inducing metalloproteinase (VLAIP). The first fraction reported to inhibit the viability of K562 cells about 30%.…”
Section: 3639mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism through which cardiotoxin-3 (CTX-3) from Naja naja atra venom exercises its effects on tumors was studied by Yang et al [ 89 ] who reported that apoptosis is followed by increased expression of Bax and endonuclease G and decreased expression of Bcl-x in K562 cells. Another report showed that CTX-3 possesses apoptotic effects through the activation of the JNK pathway and caspase-12 by triggering Ca 2+ influx, the consequence being the rapid increase in the cytosolic Ca 2+ concentration [ 90 ].…”
Section: Effects Of Bee and Snake Venom On Cancer Cellsmentioning
confidence: 99%